Study of The Azadirachta indica in Selected Siddha Text Books - Sathiyaseelan, V.; Tharshini, R. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Azadirachta indica (Neem) is an important plant in Siddha system of medicine. It belongs to Meliaceae family, in Tamil Vembu, in Sinhala Kohomba. Mention in the Siddha text books most of the diseases have been treated above medicinal plant. It is now considered as valuable source of unique natural products for development of medicines against various diseases. I have researched on these original Siddha text books such as "Sekarajahsekara Maruthuva Thiravukol", "Agasthiyar Vaithiya Sinthamani 4000" and "Pogar Vaithiyam 700". Researched was carried out from January to June 2017. Totally 690 medicinal preparations were mentioned for the above 3 books. Out of the 690 medicines, 90 preparations of medicines were used neem plant and their parts. Different part of the neem was used for the above said preparations. Based on parts used, Neem seeds were used for 52 (57.7%) variety of medicated oil preparations and Pottani (for formendation) 5 (5.5%) also, Midribs of the leaves were used for 10 (11.1%) variety of decoction preparations, bark were used for 5 (5.5%) of decoction and 3 (3.3%) of choorna preparations, flower were used for 3 (3.3%) decoction preparations and Leaves were used for 5 (5.5%) decoction preparations. Out of identified 52 oils, 26 (50%) were used external only, 9 (17.3%) were internal only and 17 (32.6%) were used internal and external preparations also. Out of identified 90 medicines, according to the combination of medicine 63 (70%) herbal preparation and 27 (30%) herbomineral preparations were recorded. Identified 90 medicines commonly used for Vatham 23 (25.5%), Suram 19 (21.1%), Saani 16 (17.7%), Valippu 6 (6.6%) and Karappan 5 (5.5%) Azadirachta indica is a non-toxic native tree. Furthermore I would like to mention some constituents liberate from the leaves prevently environmental pollution also. So, I encourage the traditional physicians, Indigenous doctors and public used to the parts of the neem tree for cure disease and step should be take conserve and replacement of the species.
Keywords: Azadirachta indica; Siddha text books; Medicines